MAPK Phosphatase 7 Regulates T Cell Differentiation via Inhibiting ERK-Mediated IL-2 Expression - Zhang, Yongliang (J Immunol, 2015)
Members of the MAPK phosphatase (MKP) protein family play critical roles in immune responses through differential regulation of MAPK activation. In this study, we show that MKP7, also known as dual-specificity phosphatase 16, was required for CD4(+) T cell responses in vivo. Mkp7(−/−) CD4(+) T cells exhibited enhanced ERK and JNK activation, and produced increased amount of IL-2 compared with Mkp7(+/+) cells upon activation. Mkp7(−/−) CD4(+) T cells were selectively defective in Th17 differentiation in vitro, which was rescued by blocking IL-2 or inhibition of ERK activation. Furthermore, mice carrying Mkp7(−/−) T cells were deficient in generation of Th17 and T follicular helper cells in vivo, and were resistant to autoimmune experimental encephalomyelitis. Our results thus demonstrate an essential role of MKP7 in effector T cell function.